Laser in-situ synthesis of high aspect ratio TiB fiber bundle reinforced titanium matrix composite coating. (July 2019) - Lin, Yinghua; Jiang, Changchun; Lin, Zhenheng; Chen, Qingtang; Lei, Yongping; Fu, Hanguang
Highlights: TiB fiber bundle with high aspect ratio can be formed in the cladding layer prepared with 0.5 μm TiB2 particles. High laser power is required to achieve TiB fiber bundle with high aspect ratio. Agglomeration of 0.5 μm TiB2 particles occurred during the solidification of the laser molten pool. Crack propagation in the fiber bundles take place in a variety of ways. Abstract: In this study, coatings are fabricated with laser cladding technique on titanium alloy substrate using TiB2 powder (0.5 μm, 5 μm and 50 μm) as the cladding materials. The effects of different TiB2 particle sizes and different laser powers on the microstructure of laser cladding layer are investigated. The results reveal that the cladding layer of high aspect ratio TiB fiber bundle is formed when using 0.5 μm TiB2 as the cladding material under the condition of high laser power (2.5 kW) of TiB fiber bundle are formed when using 5 μm and 50 μm TiB2 as the cladding materials under the condition of different laser powers. Combined with the evolution of microstructure in the cladding layers, the formation mechanism of high aspect ratio TiB fiber bundle is discussed. Meanwhile, the cladding layer of high aspect ratio TiB fiber bundle exhibits the advantages of high hardness and high wear resistance, and the predominant wear mechanisms of TiB fiber bundle are cutting and fracture.